MRSA Variant in Companion Animals - Birgit Walther; Lothar H. Wieler; Szilvia Vincze; Esther-Maria Antão; Axel Brandenburg; Ivonne Stamm; Peter Kopp; Barbara Kohn; Torsten Semmler; Antina Lübke‐Becker (2012)
Abstract Methicillin-resistant Staphylocoocus aureus (MRSA) harboring mecALGA251 has been isolated from humans and ruminants. Database screening identified this MRSA variant in cats, dogs, and a guinea pig in Germany during 2008–2011. The novel MRSA variant is not restricted to ruminants or humans, and contact with companion animals might pose a zoonotic risk.